Implementasi Supervisi Pendidikan di SDN 246 Rantebelu Kecamatan Larompong Kabupaten Luwu - Tasdin Tahrim; Firman Patawari; Ali Nahruddin Tanal (Southeast Asian Journal of Islamic Education Management, 2021)
Abstract This study aims to determine the educational supervision plan, educational supervision feedback for the principal or teacher, and the techniques used in educational supervision at SDN 246 Rantebelu Kecamatan Larompong Kabupaten Luwu. The type used in this research is descriptive qualitative. Data collection techniques are interviews, observation, and documentation study. The research subjects were teachers and administrative staff. The results showed that: (1) the education supervision plan carried out at SDN 246 Rantebelu Kecamatan Larompong Kabupaten Luwu is to prepare RPP, syllabus, list of scores, absence of annual programs and semester programs. (2) educational supervision feedback to the principal or teacher, namely verbal (verbal), providing comments on the results of direct observation of the learning process through face-to-face, no distance or equipment used. This method is usually carried out by talking to each other / dialogue, interviews, meetings, speeches, and discussions. Apart from that, giving comments can also be done indirectly through intermediary tools such as telephones, cellphones, etc. because of the distance between the speaker and the interlocutor. Non-verbal (written), providing comments on the results of observations of the learning process by means of writing without direct conversation using short, clear, and understandable language by the recipient. This method can be in the form of correspondence, sms, e-mail, learning photos, and so on. (3) There are 2 types of techniques used in SDN 246 Rantebelu Kecamatan Larompong Kabupaten Luwu, namely direct supervision, which means that the supervisor goes directly to the class to see the learning of students from beginning to end. While administrative supervision is only the administrative aspects that are assessed. Keywords: educational supervision